Financial stressors among University students in the context of COVID-19 Pandemic - Xiang-Weng, Wong; Lain-Tze, Tee; Si-Roei, Kew (Pusat Perkembangan Pelajar ,U.K.M, 2003)
Student wellness is a significant issue in universities across the country as higher education and student affairs administrators are getting more worried about financial stress among university students. Identifying students with financial stress and directing efforts to reduce financial stress among them can be executed by spotting the causes of financial stress. This study aims to determine factors influencing financial stress in 100 university students during the COVID-19 pandemic in Malaysia. Factors studied include financial self-efficacy, family background and daily expenses which might influence financial stress among university students. The results show that financial self-efficacy, family background and daily expenses have a significant relationship with financial stress among university students. That is, poor financial self-efficacy, high family stress and high daily expenses lead to increased financial stress among university students during the COVID-19 pandemic in Malaysia. This study is able to provide several important implications to policymakers, academics and students.